Niveles de ventas de la Empresa Ziwis S.A del cantón Babahoyo durante el periodo 2023. - Inga Mora, Rina Isabel (2024)
The case study entited “Sales levels of the compay Ziwis S.A. in Babahoyo during the period 2023” is dedicated to offer laboratory services for the different clinical análisis required by the client. The objective of the study is to evaluate the sales indexes in order to detect the shortcomings that occur in the laboratory. In addition, the comparative análisis method was applied because it favors to contrast the sales levels abtained in the two previous periods and thus observe the evolution of their income if they have increased or decreased, emphasizing the factors that influence the economic growth of the organization. Therefore, the techniques applied in the case study were: the comparative table and the interview, obtaining relevant and accurate information to address this problema. This case study is contextualized according to the guidelines proposed by the Babahoyo Technical University, through which it evaluates and analyzes the elements on which the problems encountered in Ziwis S.A are based. Consequently, it has identified low income and increased its expenses and expenditures in which it is not profitable enough to achive its aspirations focused on the goals. In addition, the factors that influence in one way or another their economic performance were identified such as market competition, the ability to innovate, trends in the health area, changes in policies and maintenance costs of the equipment used in the clinical laboratory. Other importants aspects are described later in the development of the case study.